PENERAPAN BALANCED SCORECARD SEBAGAI ALAT PENILAIAN KINERJA PADA PRIMKOP POLRESTABES SEMARANG - Cahyadi, Puas; Indarto, Indarto; A.J, Dyah Nirmala (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
Abstract. The purpose of the study was to assess the performance of Primkop Polrestabes Semarang using the Balanced Scorecard method covering financial, customer, internal business processes, as well as learning and growth perspectives. This type of research is descriptive quantitative by describing the research data that has been obtained from the four perspectives. Data was collected by using documentation, questionnaire, interview and Focus Group Discussion (FGD) methods. The research step begins by translating the vision and mission into strategic bjectives, measures of achievement, performance targets and the weight of each perspective. The next step is to calculate the score for each perspective. Then calculate the total score of the four perspectives into a Balanced Scorecard score and determine the cooperative performance criteria. Based on the results of the study, it is known that the performance of Primkop Polrestabes Semarang for the 2018-2020 period is in the